Seeking Understanding on the Issue of Happiness: A Hermeneutic Literature Review - Petersen, Matthew (Auckland University of Technology, 2017)
The body of literature relating to human happiness is historically rich and is gaining increasing relevance in the current healthcare environment. Although the term happiness is commonly used in society this dissertation illustrates the complexities of happiness, highlighting its associations with what are understood as desirable states of being, as well as social constructs which appear more related to suffering than well-being. Five key areas are looked at, these are: conceptions of happiness, “unhelpful happiness”, longer term happiness, short term happiness and barriers to happiness. A hermeneutic methodology is adopted providing personal reflections to develop further understanding and provide considerations for psychotherapists.
Keywords: Happiness; Psychotherapy; Understanding happiness; Hermeneutic Literature Review